The influence of group counseling services with thought stopping techniques in reducing public speaking anxiety in students - Dermawan, Oki; Kardinah, N; Defriyanto, Defriyanto; Busmayaril, Busmayaril; Anggun, Tarisa (Universitas Islam Negeri Raden Intan Lampung, 2024)
This study on the influence of group counseling services with thought stopping techniques in reducing public speaking anxiety among students at SMPN 1 Abung Surakarta is motivated by the issue of students experiencing anxiety when speaking in public. The aim of this research is to determine the impact of thought stopping techniques in reducing public speaking anxiety among students at SMPN 1 Abung Surakarta. This research uses a quantitative approach with an experimental research type. The design employed is a one-group pretest-posttest design. The population in this study consists of 30 students from class VII C at SMPN 1 Abung Surakarta. The sampling technique used is purposive sampling, selecting 8 students as the experimental group based on the results of a high-category scale completion. The subjects received counseling six times. The instrument for data collection is a public speaking anxiety scale. The data analysis technique used is non-parametric statistical analysis with the Wilcoxon test. The results of this study show that the thought stopping technique is effective in reducing public speaking anxiety. This is evidenced by the Wilcoxon test results, which showed a value of (Z = -2.527) with an Asymp.Sig. (2-tailed) value of 0.012. This indicates that public speaking anxiety decreased after the group counseling services with thought stopping techniques were administered.